Variabilidade de longo prazo de juvenis dos camarões rosa Farfantepenaeus brasiliensis (Latreille 1817) e F. paulensis (Pérez-Farfante 1967) (Decapoda: Penaeidae) e dinâmica populacional na Enseada de Ubatuba, SP, Brasil - Perroca, Júlia Fernandes (2019)
Farfantepenaeus brasiliensis and F. paulensis are commonly exploited in the north of São Paulo because of their commercial value. The evaluation of the state of conservation of these species is difficult to perform, since both are landed as pink shrimp, which generates scarce data and makes impossible reliable ecological analyzes. Thus, this study evaluated through Generalized Additive Models (GAMs) the juvenile catches per unit of effort in abundance (CPUEn) and biomass (CPUEw) of these species and their relationships with environmental factors in the Ubatuba Bay in an interval of 22 years (1995 to 2017). The F. paulensis CPUEn model showed high catches recorded in months of the first semester and a strong influence of years under such monthly patterns. Also, there was a greater abundance in increased pluviosity, Phi < 4.5 and in moderate and strong La Niña and El Niño. CPUEw varied through the years, with increase in biomass from 2005, and in rainy periods. The F. brasiliensis CPUEn model presented high abundance from January to May, specially from 2010. Higher catches were also recorded in El Niño events, as well in Phi < 4.5 and OM < 15. CPUEw was mainly influenced by Phi. Although juveniles of both species were present in the bay during the months prior to the closure season it seems that there is maintenance of populations.